Pengaruh Kemajuan Teknologi, Literasi Keuangan, Dan Persepsi Kemudahan Terhadap Keputusan Penggunaan Transaksi Digital (E-Wallet) Pada Konsumen Toko Pd Sahabat Pameungpeuk Garut - Sarah Apriani; N. Neni Triana; Thomas Nadeak (Management Studies and Entrepreneurship Journal (MSEJ), 2023)
This study aims to analyze the influence of technological advances, financial literacy, and perceived convenience on the decision to use digital transactions (e-wallets) for consumers at PD Sahabat Pameungpeuk Garut Shop. This study used a descriptive verification method with a quantitative approach, sampling was carried out using a non-probability sampling method, namely purposive sampling technique and using the slovin formula. This research was conducted using a survey method using a Likert scale questionnaire which was distributed to 100 respondents to consumers at the PD Sahabat Pameungpeuk Garut Shop. The data analysis technique used is path analysis with partial and simultaneous hypothesis testing. The results showed that the correlation between the X variables all showed a positive and significant correlation. While partially technological progress shows negative results on the decision to use e-wallet digital transactions, then for financial literacy and perceptions of ease it produces a positive and significant value on the decision to use e-wallet. Simultaneously that between technological advances, financial literacy, perceived convenience has a significant effect on the decision to use e-wallet digital transactions.